2016
DOI: 10.1039/c6py01882c
|View full text |Cite
|
Sign up to set email alerts
|

Combination anti-HIV therapy via tandem release of prodrugs from macromolecular carriers

Abstract: Reversible addition-fragmentation chain transfer (RAFT) polymerisation has been used to create a library of copolymers outfitted with a combination of self-immolative reverse transcriptase inhibitor prodrug pendents comprising zidovudine (AZT) and lamivudine (3TC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…So far, the examples shown usually involve two drug molecules maximum, however, it might be interesting the use of polymer chains bearing pendant cleavable disulfide-based prodrugs, so more drug molecules could be delivered. In particular, this approximation has been found to be successful in treating HIV, since it is possible to carry multiple drugs at a time thus leading to a more effective combination therapy [36,61]. Following a similar approximation, a polyethylene glycol block bearing a small amount of prodrugs (doxorubicin) on its side chain has been reported.…”
Section: Prodrugs Based On Self-immolative Spacersmentioning
confidence: 93%
“…So far, the examples shown usually involve two drug molecules maximum, however, it might be interesting the use of polymer chains bearing pendant cleavable disulfide-based prodrugs, so more drug molecules could be delivered. In particular, this approximation has been found to be successful in treating HIV, since it is possible to carry multiple drugs at a time thus leading to a more effective combination therapy [36,61]. Following a similar approximation, a polyethylene glycol block bearing a small amount of prodrugs (doxorubicin) on its side chain has been reported.…”
Section: Prodrugs Based On Self-immolative Spacersmentioning
confidence: 93%
“…SFP is therefore a promising nano/microcarrier for safe drug delivery which may pave room for new opportunities to explore other drug conjugates. Among other studies, Daniel et al have reported that drug conjugates especially polymer conjugates are potentially suitable for the delivery of antiviral drugs [109,110]. A typical example is the synthesis of poly(lactideco-glycolide) nanoparticles loaded with a combination of reverse transcriptase and protease inhibitors.…”
Section: Mechanism Of Cleavage Methods Of Hydrolysis Referencesmentioning
confidence: 99%
“…As human serum albumin comprises a single active cysteine residue (Cys-34) and constitutes up to 80% of serum thiols, potentially undergoing disulfide exchange prematurely causing antiviral prodrug release before cell uptake. Polymerdrug conjugates with unhindered disulfides linked to antiviral prodrugs showed stability in the presence 0.5 mM human serum albumin at 37°C and in turn suggests that drug release is selective upon cell i nternalization [23].…”
Section: Successful Disulfide Conjugatesmentioning
confidence: 99%